Integrated Versus Subordinated: Public Relations Application In Faith-Based Women Organization - Kholifatul Fauziah (LP2M Universitas Sarjanawiyata Tamansiswa, 2020)
This paper offers a critical interpretation of public relations (PR) generic principles application in faith-based women organization. In particular, this paper examines whether this organization should manage PR in separate management. This study takes up the PR application in the Central Board of Aisyiyah (CBA) since it subordinated the PR function to a secretary in the administrative period from 2010 down to date, whereas it engaged with PR as a single department on 2005-2010. This subordination turns into vice versa application of the generic principle because if the significant contribution of PR considered, its application pattern should be run from subordinative, as a part of another department, into an integrative management function. Therefore, this paper elaborates on the PR application in both periods and the factors working on it. The research method was a case study using the four models of PR, from Hunt and Grunig, as an analysis framework. The results indicate that there is no significant difference between the period of subordination and before. The factors that influenced its applications are knowledge and skill, shared expectations, participative culture, and organizational identity. Thus, the results have theoretical and practical implications for PR application in faith-based women organizations.Keywords: Public Relations Application, The Four Models, Aisyiyah, Faith-Based WomenOrganization.